Metabolism features and milk microbiota of cows with mastitis in the Amur Oblast - M. E. Ostyakova; I. S. Shulga; V. K. Irkhina; K. S. Kositsyna; N. S. Golaydo (Ветеринария сегодня)
The effective management practices of dairy farming are inextricably linked with the production of high quality milk, while the mastitis is one of the causes of reductions in milk yields and quality. The aim of the work was to study the microbiological profile of milk, the sensitivity of isolated microorganisms to antibiotics and metabolism features of cows with mastitis in the Amur Oblast. The following microorganisms were identified in the milk samples from cows with mastitis: Staphylococcus epidermidis (34.69%); microbial associations: Streptococcus agalactiae + Escherichia coli (32.65%) and Staphylococcus saprophyticus + Streptococcus agalactiae + Escherichia coli (30.61%); Staphylococcus haemolyticus (2.05%). Microorganisms isolated from the milk of mastitis-affected cows were susceptible to the following antimicrobials: Escherichia coli to cefotaxime (28.00 ± 2.00 mm) and ceftriaxone (27.50 ± 0.35 mm); Staphylococcus epidermidis, Staphylococcus haemolyticus, Staphylococcus saprophyticus to cefotaxime (35.50 ± 0.18 mm) and amoxicillin (35.10 ± 0.35 mm); Streptococcus agalactiae to tetracycline (27.60 ± 1.17 mm) and gentamicin (26.40 ± 0.99 mm). Metabolic disorders were observed in cows with mastitis. The albumin-globulin ratio was reduced (0.41), which is typical for various inflammatory processes; and a low albumin levels (29.00 ± 0.89%) suggested a decreased protein synthesis in hepatocytes. A moderate increase in gamma globulins (47.60 ± 1.05%) was associated with stimulation of the phagocytic mononuclear system. Water and mineral metabolism disorders were confirmed by low levels of calcium (1.80 ± 0.03 mmol/L) and magnesium (0.70 ± 0.02 mmol/L), which is a sign of many pathological conditions, and is associated with heavy lactation. Calcium-phosphorus ratio was reduced (0.82). Hematological indicators suggested hypochromic anemia (hemoglobin level – 100.60 ± 1.28 g/L, globular value – 0.60 ± 0.01). The leukogram was indicative of lymphocytopenia (36.90 ± 2.60%) and neutrophilia (rod-shaped neutrophils – 1.80 ± 0.13%, segmented neutrophils – 51.80 ± 2.51%).